Fertility differentials between Korean and international marriage couples in South Korea. Issue 1 (2nd January 2018) - Kim, Hyun Sik
ABSTRACT: Amid high hopes that the rise of international marriage will boost fertility rates in South Korea, this article assesses fertility differentials between Korean and international marriage couples. Espousing the theoretical position that fertility decisions need to be viewed from a couple perspective, we seek to build a new framework that goes beyond the traditional immigrant fertility literature. To test the formulated hypotheses, we compared fertility hazards among four couple types using the 2012 National Survey on Multicultural Families and the 2012 National Fertility Survey: couples consisting of a Korean wife and a Korean husband (Korean couples), couples consisting of a foreign wife and a Korean husband (foreign-wife couples), couples consisting of a Korean wife and a foreign husband (foreign-husband couples), and couples consisting of a foreign wife and a foreign husband (foreign couples). The results from Cox regression models revealed that the wives of Korean couples experienced the highest fertility hazards for the first birth, followed by the wives of foreign-wife couples. Furthermore, wives of Korean couples took the shortest time to give birth to the second child, followed by wives of foreign-husband and then foreign-wife couples. We discussed theoretical bearings of these findings and outlined a promising line of further research.